Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Emosional Anak di Taman Kanak Kanak Awalidil Jannah Timbulun Kabupaten Pesisir Selatan - Indah Febriani; Yulsyofriend Yulsyofriend (Jurnal Family Education, 2022)
Childhood is the golden age forearly childhood. At this age, all aspects of child development develop very rapidly. Various factors are involved in the development of the child's emotional intelligence index. One of these is the ability of parents to assign appropriate parenting patterns to their children to promote their child's development of emotional intelligence. The purpose of this study was to find out the relationship between parents and parents to the emotional development of their children in kindergarten Awalidil Jannah Timbulun District Coastal South.type of research Thisis correlated and use quantitativemethods, the population in this study were all students in Kindergarten Awalidil Jannah Timbulun thedistricts Coastal South. The sample of this study covers the entire population, the number of samples is 42 respondents. Data collection method using questionnaires and documents. The results showed that there was a significant relationship between parenting patterns on emotional development Children in Awalidil Jannah arise in Kindergarten, South Coast District . The correlation test result is Sig 0.017 < 0.05. This means that there is an important relationship between parenting styles and children's emotional development. The results of the correlation analysis show that the product coefficient has a negative correlation coefficient of 0.367 and a significance value of 5%. The relationship between the two variables is a negative relationship